Detaching cells in culture medium using forced vibration for removing a centrifugation from culture process - Shimoguchi, Hayato; Imashiro, Chikahiro; Takemura, Kenjiro (Frontiers in Acoustics, 2024)
Recent advancements in cell culture have significantly impacted various fields, including drug discovery and regenerative medicine. Consequently, there is an increasing need to minimize the contamination risks and labor involved in cell culture processes. Traditional cell detachment methods typically employ proteolytic enzymes followed by centrifugation to remove these enzymes after cell detachment. This process often requires numerous manual interventions which can lead to potential contamination and deterioration of cell quality. In this study, we propose a novel cell detachment method that eliminates the need for centrifugation even with less trypsinization time. Our approach involves reducing the duration of trypsinization, collecting the trypsin before complete cell detachment, and subsequently detaching the cells using forced vibration within the culture medium. We conducted experiments to optimize the enzyme treatment time and vibration conditions. Our results demonstrated that this method achieved an 82.8% detachment rate of cells from the culture surface. These findings indicate that the proposed cell detachment technique is effective in removing cells from the culture substrate and the following subculture process without the need for centrifugation.